Do aluminum (Al)-hyperaccumulator and phosphorus (P)-solubilising species assist neighbouring plants sensitive to Al toxicity and P deficiency? - Delgado, M.; Barra, P. J.; Berrios, G.; Mora, M. L.; Durán, P.; Valentine, A.; Reyes-Díaz, M. (Frontiers in Plant Science, 2024)
We aimed to evaluate the facilitation effects of an aluminum (Al) hyperaccumulator species bearing cluster roots, Gevuina avellana, on the seedling growth and performance of an Al-intolerant and Pdeficient-sensitive plant, Vaccinium corymbosum. For this, seedlings of G. avellana and V. corymbosum were grown alone or together as follows: i) 2 G. avellana seedlings, ii) 1 G. avellana + V. corymbosum and iii) 2 V. corymbosum, in soil supplemented with Al (as Al2(SO4)3) and in the control (without Al supplementation). We determined relative growth rate (RGR), photosynthetic rate, chlorophyll concentration, lipid peroxidation and Al and nutrient concentration (Nitrogen (N), P, potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), Al and sulfur (S)) in leaves and roots of both species. The results showed that, in general, G. avellana did not assist V. corymbosum to enhance its RGR nor reduce its Al uptake. However, G. avellana assisted V. corymbosum in enhanced N acquisition and, consequently, to increase its chlorophyll concentration and photosynthetic rate. Besides, V. corymbosum had lower lipid peroxidation in leaves when grown in the soil with high Al supplementation in association with G. avellana. Our results suggest a facilitating effect of G. avellana to V. corymbosum when grown in soils with high Al concentration, by enhancing chlorophyll concentrations and photosynthetic rate, and decreasing the oxidative damage to lipids.